(untitled) (TAMADDUN NURI JURNALI, 2025)
This article provides detailed information about the culture and customs of the Republic of Korea. Korean culture has a history of almost a thousand years, it is distinguished by its unique origins, traditions, art, music and gastronomy. This study analyzes the main elements of culture, traditional holidays, religious practices and changes in modern social life.